Dorsopathies: a new view of the problem of diagnosis and treatment - N A Shostak; N G Pravdyuk; N A Shostak; N G Pravdyuk (Современная ревматология)
The paper shows the newest aspects of the diagnosis and treatment of the most important varieties of dorsopathies: inflammatory spondylopathies and spondylosis.